The Eisenhawer Doctrine (1957): The Impact on Arabic Countries and The Soviet Union Attitude (Raparin Journal of Humanities (RJH), 2020)
Following the end of World War II, and emerging of a vacuum after the withdrawal of British and French forces from some of the Middle East countries in the region, creating fear in Western countries, particularly the United States, that the Eastern Bloc, in particular Russia, would seek to fill the vacuum and spread the idea of leftism and communism in the region. For this reason, the United States has made every effort to confront the idea of communism and establish a foothold in the region among its policies. To this end, then US President Harry Truman announced his country's new policy in the context of the Truman project on the Middle East in (1945). Following Harry Truman, when Eisenhower assumed power as the new US president in (1953), he put forward the new policy of his country named Eisenhower’s Dwight in Congress in order to confront Russian politics and infiltrate communist thought in the area. There were several items in his project that emphasized the cooperation of Middle Eastern countries, especially in the economic and military fields.      The Eisenhower’s Dwight has had a variety of reactions from countries in the region, especially Arab countries. Some have accepted it from the very beginning. Some also expressed opposition to the project. There were also countries that initially opposed the Eisenhower project, but after a period of time following US efforts and pressure, eventually endorsed the project and became a fan of the US. As a result of these political divisions in the region, several political and military alliances between the countries of the Middle East Were formed. The idea of Nasser and the idea of Arab nationalism come to life at this time. Although originally favored by the Eastern Bloc, especially Russia, it also partially weakened the notion of communism and was about to cause tension between proponents of these two ideas. This situation had nothing in fact to do other than destabilizing the political state and the occurrence of several coups in order to change the regime of some of Middle Eastern countries, besides the long sovereignty of some Arab rulers.Regarding the Soveit Union attitude towards the Eisenhower’s doctrine, it can be seen that,the Soveit Union ctitisized  by the Soviet authorities from internal and external the SoveitUnbion.For instance the The Soveit Union attempted to gain extermal allies among the Middle Middle Eastren countries to convince them this doctrine is a part previous imperliams that supported by Westren countries.Finally,in the United Nation,The Soveit attempted to make a campaign to remove this doctrine as it mention a therat of world peace.